(untitled) (London Journal of Engineering Research, 2024)
Large-scale road construction in mountainous areas inevitably leads to numerous excavation slopes, particularly in the Loess Plateau, characterized by abundant ancient landslides and complex stratigraphy. Excavation-induced stress relief can easily reactivate these ancient landslides, posing significant threats to engineering safety. This study takes an ancient landslide in the Loess Plateau as a case example. Field investigations clarified the lithological characteristics of the strata. Indoor triaxial unloading tests were conducted to examine the unloading creep behavior of silty soil and clay located near the sliding zone. Finally, numerical simulations were employed to analyze the evolution process of landslide reactivation induced by excavation. The study revealed the following findings: (1) The primary factor inducing the landslide is the differential unloading creep behavior of silty soil and clay. Silty soil readily reaches an accelerated creep state under unloading conditions, whereas clay remains relatively stable with smaller deformation. The creep behavior of the soil can be well described using the Nishihara model. (2) Comparison of two unloading stress paths showed that vertical stress unloading causes minor rebound deformation with minimal impact on overall deformation. In contrast, lateral stress unloading results in significant soil deformation, which is the main cause of the landslide. (3) During the landslide, there was an abrupt change in pore water pressure within the soil, which can be combined with deep soil deformation as a key indicator for monitoring and early warning of this type of landslide.